Impact of Sport on the Course of Endometriosis - Niemirka, Szymon; Janiak, Aleksandra; Dominiczak, Kinga; Grądalski, Łukasz; Dębicki, Filip; Kopaczyńska, Adrianna; Szafrańska, Katarzyna (Quality in Sport, 2024)
Endometriosis is a common condition affecting approximately 10% of women of reproductive age and leads to many unpleasant symptoms, such as pelvic pain, painful intercourse, and fertility issues. Although treatment primarily involves surgical and hormonal approaches, growing evidence suggests that physical activity may play a beneficial role in alleviating symptoms of the disease. The aim of this paper is to review the literature on the impact of physical activity on the symptoms of endometriosis and evaluate the role of exercise in improving the quality of life for patients. Available research indicates that regular physical activity, including aerobic and strength exercises, can reduce pain intensity, improve well-being, and decrease the need for pain medications. Additionally, exercise positively affects mental health, reducing stress, anxiety, and depression, which, in turn, improves the course of the disease. The findings suggest that physical activity should be considered an integral part of endometriosis treatment, serving as a supportive therapeutic approach. However, further controlled studies and long-term observations are necessary to determine the optimal type, intensity, and frequency of exercise for women with endometriosis.